A clinico-epidemiological profile of neonates with birth asphyxia in SNCU and NICU of a tertiary care hospital with special reference to renal parameters and serum calcium levels in birth asphyxia - Pattanayak, Ujjwal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Birth asphyxia accounts for around 23% of annual neonatal deaths in the developing world. Perinatal asphyxia or birth asphyxia as is more commonly used is one of the most common presentations of a neonate in Special Newborn Care Units (SNCUs) and Neonatal Intensive care Units (NICUs) all around the world. The main objective of the study was to study electrolyte status and renal parameters in asphyxiated newborns of different severity in early neonatal period and to determine the occurrence of renal failure in asphyxiated neonates and to correlate severity with Apgar score and hypoxic ischaemic encephalopathy grading of neonates. Methods: The present study was a Prospective Cross-Sectional Hospital based single centre study conducted in the Department of Paediatrics, Midnapore Medical College, Paschim Medinipur, West Bengal, India. Term, appropriate for gestational age babies born/admitted in SNCU and NICU with birth asphyxia between January, 2020 to June, 2021 were included in the study. Results: Our study showed that, in control group 1 (60%) were male and 6 (40%) were female. In case group 18 (51.4%) were male and 17 (48.6%) were female. Among 35 cases renal failure is seen in 68.57 % and none of the controls had renal failure. Oliguria >0.5 ml/kg/hr was found in 14 (93.3%) patients in the control group, in case group it was found in 32 (91.4%) patients. The incidence of renal failure is highest with moderate asphyxia accounting for 41.67%. Conclusions: Perinatal asphyxia is one of the commonest cinical conditions encountered in the sick neonate. It affects almost all organ systems of the body. As the pre renal type of kidney injury is more common, these babies usually recover fully with fluid resuscitation in majority of cases.